ENHANCING ENGLISH WRITING SKILLS IN ENGINEERING STUDENTS THROUGH A FLIPPED CLASSROOM APPROACH. - Pathan, Soebmahamed Y; Qureshi, Vaseem (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Students in the 21st century are looking for an educational system that supports their needs. The focus of teaching has shifted from being teacher-centered to student-centered through innovative methods. With technology and globalization advancing, strong communication skills in English are crucial for engineering students as they are key for employability. Communication is one of the 12 essential Programme Outcomes defined by the National Board of Accreditation (NBA). The four fundamental language skills—listening, speaking, reading, and writing (LSRW)—play a significant role in developing English communication abilities. While all these skills are important, writing serves as a foundation for effective verbal communication, yet it can be challenging to master without a solid grasp of the other three skills. This paper investigates how the Flipped Classroom approach can be effectively applied in English language classrooms to enhance the writing skills of 30 Third-Year B.E students, along with other essential 21st-century skills. Background: The current teaching methods have evolved from traditional lectures to incorporating cooperative and collaborative learning, along with Information and Communication Technology in English classes. Some effective approaches include computer-assisted language learning, mobile-assisted language learning, project-based and problem-based learning, flipped classrooms, and task-based language learning. The present study examines how well the flipped classroom model helps improve undergraduate students' writing skills. The study focused on a group of college students enrolled in a writing course. In the flipped classroom approach, students watched recorded lectures and completed online activities before attending in-person classes. During these classes, they worked on writing tasks with their instructor's help. The research used a mixed-methods design, which included analyzing data from tests taken before and after the course to measure changes in writing skills. It also gathered student opinions through surveys. The results suggest that the flipped classroom approach is effective in improving students' writing. The test scores showed a significant improvement in their writing skills, and the students reported that the method was engaging, flexible, and beneficial for their learning. In conclusion, this study emphasizes the potential of the flipped classroom model to enhance writing skills in undergraduate students.